THE AESTHETICS OF EXTERNAL RHYTHM, THE POETRY OF IBN AL-NAQEEB AL-FAKISI (D 687 AH) - Dalal Hussein Khudair; Orooba Khalil Ibrahim al-Dabbagh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Praise be to God alone, and prayers and peace be upon the master of creation, our beloved, the chosen one, the enlightening lamp, and upon his good and pure family. As for what follows: